TYPE 2 MYOCARDIAL INFARCTION - Mitevski Goran; Nikolovski Robert; Furnadjiski Atanas; Manev, Nikola; Georgiev, Antonio (MIT University Skopje, 2023)
Myocardial injury is when there is elevated cardiac troponin values at least one value above the upper reference limit (URL). Causes of elevated troponin can be sustained bradyarrhythmia, hypotension, shock, respiratory failure, anemia, tachyarrhythmia, hypertension, heart failure, defibrillator shocks, sepsis, chronic kidney disease, stroke, subarachnoid hemorrhage, pulmonary embolism, pulmonary hypertension, infiltrative disease (amyloidosis, sarcoidosis..), chemotherapeutic agents, critically ill patients, strenuous exercise, cardiac ablation, cardiomyopathy, coronary spasm, microvascular dysfunction, atherosclerotic plaque disruption with thrombosis, etc. When it is associated with myocardial ischemia it is designated as myocardial infarction (MI). Type 2 myocardial infarction occurs due to disturbed oxygen supply and/or unbalanced demand. There are no conditions that are characteristic for type 1 MI such as plaque, rupture and thrombosis
Keywords: type 2 MI; causes; risk factors; treatment; prognosis